PENGARUH KECUKUPAN MODAL, PROFITABILITAS, DAN EFISIENSI TERHADAP ZAKAT PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING - Walidah, Ziyana; Sujianto, Agus Eko (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2024)
This research is motivated by the lack of financial performance discipline in paying zakat in Islamic banking. Not all Islamic banks in Indonesia fulfill their obligations in issuing corporate zakat. This is judged by the very essential position of Islamic banking, and is a good example for companies in issuing zakat in order to help the welfare of the community. The purpose of this study is to examine the effect of financial performance ratios, namely capital as proxied by Capital Adequacy Ratio (CAR), profitability as proxied by Return Of Assets (ROA), efficiency as proxied by Expenses/Operational Income to Islamic banking zakat. The approach in this study uses quantitative methods, with this type of research using associative. The sampling technique used purposive sampling, with secondary data. The data source uses the company's annual report recorded at the Financial Services Authority for the 2011-2020 period. The analytical methods used in this study include (1) Descriptive Statistics, (2) Test Models; (3) Classical Assumption Test, (4) Hypothesis Testing; (5) Moderation Regression Analysis. The analytical tool used in this research is EViews 10. The results showed that (1) CAR had no significant effect on corporate zakat (2) ROA had a significant effect on corporate zakat (3) BOPO had no significant effect on corporate zakat (4) company size was unable to moderate CAR on corporate zakat (5) company size unable to moderate ROA on corporate zakat; (6) the size of the company is able to moderate the BOPO against corporate zakat.